Book Reviews. Issue 2 (1st March 2017) - Anders, Ellen; Becker, Annette; Becker, Annette; Brewster, Maureen; Kinley, Tammy; Delgado, Henry Navarro
COSTUME DESIGN SINCE 1945: HISTORICAL DRESS FROM COUTURE TO STREET STYLE, DEIRDRE CLANCY (2015) 2nd ed. London: Bloomsbury Publishing, 280 pp., ISBN: 9781472539403, h/bk/ ISBN: 9781472524249, p/bk, €21.99THE DRESS DETECTIVE, INGRID MIDA AND ALEXANDRA KIM (2015) London and New York: Bloomsbury Academic, 224pp., ISBN: 9781472573971, p/bk, 39.95THE FIRST BOOK OF FASHION: THE BOOK OF CLOTHES OF MATTHÄUS & VEIT KONRAD SCHWARZ OF AUGSBURG, ULINKA RUBLACK AND MARIA HAYWARD (EDS) (2015) London and New York: Bloomsbury Academic, 410pp., ISBN: 9780857857682, h/bk, 38.99THE BIRTH OF COOL: STYLE NARRATIVES OF THE AFRICAN DIASPORA, CAROL TULLOCH (2016) 1st ed., London and New York: Bloomsbury Academic, 254 pp., ISBN: 9781859734704, p/bk, 34.95DRESS, FASHION AND TECHNOLOGY: FROM PREHISTORY TO THE PRESENT, PHYLLIS G. TORTORA (2015) London: Bloomsbury Academic, 245 pp., ISBN: 9780857851901, h/bk, 102.00/ISBN: 9780857851918, p/bk, 27.99STREET STYLE: AN ETHNOGRAPHY OF FASHION BLOGGING, BRENT LUVAAS (2016) London: Bloomsbury Academic, 336 pp., ISBN: 9780857855756, p/bk, £19.99